Isolated spontaneous renal artery dissection: Endovascular intervention - J Gregory Roberts; Chadwick Michaels; Danarae Vasquez; Alexander Warneke (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Isolated spontaneous renal artery dissection (ISRAD) is a rare clinical phenomenon that typically presents with refractory hypertension and abdominal and flank pains but may also induce hematuria and severe headache. The protean manifestations of ISRAD may be misinterpreted as renal colic or intrabdominal pathology and requires a high index of clinical suspicion. Computerized tomography (CT), coupled with angiography (CTA) clarifies the diagnosis. No evidence-based management exists as intervention is reserved for persistent symptoms despite optimal medical treatment. The sporadic incidence remains limited to but a few cases illustrating endovascular management. Herein between 2014 and 2019 are presented three, healthy Caucasian males, ages from 47 to 54 years-old who presented with symptomatic ISRAD, coupled with limited renal infarctions, and treated with mid-renal and segmental arterial stenting.